2014
DOI: 10.1556/avet.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin alters steroid secretion but does not affect cell viability and the incidence of apoptosis in porcine luteinised granulosa cells

Abstract: The compound 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a by-product of human industrial activity, was found to affect ovarian steroidogenesis in animals, but the mechanism of its action is still unclear. The aims of the study were to examine the effect of TCDD on (1) progesterone (P 4 ) and oestradiol (E 2 ) production by granulosa cells isolated from medium (3-6 mm) and preovulatory (≥ 8 mm) porcine follicles, (2) the viability of the cells, and (3) the incidence of apoptosis. Porcine granulosa cells were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In the present study, we were focused on identifying all possible pathways (molecules) involved in the mechanism of TCDD action in porcine granulosa cells and, therefore, the selected dose of TCDD (100 nM) moderately exceeded its environmentally relevant concentrations. The concentration of 100 nM of TCDD was previously reported to affect porcine granulosa cells steroidogenesis (Gregoraszczuk et al, 2000;Gregoraszczuk, 2002;Jablonska et al, 2014), gene expression (Piasecka-Srader et al, 2016;Sadowska et al, 2017;Nynca et al, 2019), lncRNA expression (Ruszkowska et al, 2018) and proteome (Orlowska et al, 2018) without affecting cell viability and morphology. Moreover, 100 nM was one of the two most frequently used TCDD concentrations in in vitro experiments performed on porcine ovarian cells.…”
Section: Tcdd Treatment Of Granulosa Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, we were focused on identifying all possible pathways (molecules) involved in the mechanism of TCDD action in porcine granulosa cells and, therefore, the selected dose of TCDD (100 nM) moderately exceeded its environmentally relevant concentrations. The concentration of 100 nM of TCDD was previously reported to affect porcine granulosa cells steroidogenesis (Gregoraszczuk et al, 2000;Gregoraszczuk, 2002;Jablonska et al, 2014), gene expression (Piasecka-Srader et al, 2016;Sadowska et al, 2017;Nynca et al, 2019), lncRNA expression (Ruszkowska et al, 2018) and proteome (Orlowska et al, 2018) without affecting cell viability and morphology. Moreover, 100 nM was one of the two most frequently used TCDD concentrations in in vitro experiments performed on porcine ovarian cells.…”
Section: Tcdd Treatment Of Granulosa Cellsmentioning
confidence: 98%
“…Since TCDD influences the production of estrogens and progesterone by porcine granulosa cells (Gregoraszczuk, 2002;Jablonska et al, 2011;Jablonska et al, 2014), it is of importance to identify its molecular targets in follicular cells. The results of our previous studies, performed on porcine granulosa cells, demonstrated, among others, that TCDD affected the expression of transcripts involved in the follicular atresia as well as cell proliferation and cell cycle regulation (Sadowska et al, 2017;Ruszkowska et al, 2018;Nynca et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the congeners are proved to be highly toxic, but 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) is the most toxic congener, and probably the most toxic compound ever synthesized by man, being widespread and highly persistent in the environment, and accumulating in living organisms, especially in fat tissue. The dioxins are known to adversely affect the reproductive system in part due to their ability to alter hormone levels in many species [84,85]. …”
Section: Dioxins and Endometrial Cancermentioning
confidence: 99%
“…TCDD is widespread and highly persistent in the environment and accumulates in living organisms, especially in fat tissue. The dioxin is known to adversely affect reproduction in part due to its ability to alter hormone levels in many species, including pigs [ 7 , 8 ]. Previous studies indicate that most of TCDD effects are mediated through the aryl hydrocarbon receptor (AhR), a ligand-activated member of the bHLH-PAS family of transcription factors [ 9 ].…”
mentioning
confidence: 99%
“…Therefore, the goal of this study was to establish the influence of low doses of TCDD and genistein used in combination on porcine granulosa cells in vitro . Since extensive dose dependent studies on porcine granulosa cells have been already performed individually for genistein [ 5 , 15 , 16 ] and TCDD [ 7 , 8 , 17 ], the current study was focused on the examination of the combined effects of the low but environmentally relevant doses of the two treatments. Thus, the specific objectives were to examine the effects of TCDD (100 pM) and/or genistein (500 nM) on: 1) progesterone (P 4 ) and estradiol (E 2 ) production; 2) dynamic changes in expression of AhR (mRNA and protein); 3) dynamic changes in expression of ERβ (mRNA and protein); and 4) induction of apoptosis in porcine granulosa cells derived from medium (3–6 mm) porcine follicles.…”
mentioning
confidence: 99%